Efficacy of the Hibiscus surattensis L. Leaves Active Fraction in Reducing the Levels of HbA1c, AGEs, and Glucose Uptake in Muscle Cells of Diabetic Type 2 Model Rat - Susanto, Yuliet; Sukandar, Elin Yulinah; I Ketut Adnyana; Tandi, Joni (Indonesian Journal of Pharmacy, 2022)
Hibiscus surattensis L. is a traditional medicinal plant often used for diabetes treatment in Indonesia, especially in Central Sulawesi. The leaves contain mainly kaempferol, morine, and trifolin which have various pharmacological effects, including high antioxidant properties and the potential to increase insulin secretion. Therefore, this study aims to investigate the efficacy of the Hibiscus surattensis L. leaves (HSL) active fraction in reducing the levels of HbA1c, AGEs, and GLUT-4 expression in the muscle tissue of rat model with type 2 diabetes mellitus using a high-fat and fructose diet of 1.8 g/kg BW (HFD/HF) for 8 weeks. A total of 20 male rats were randomly assigned into four groups namely (1) normal control diet with standard rat chow; (2) negative control with HFD/HF diet; (3) treatment group with metformin 100 mg/kg BW as standard; (4) treatment group given HSL active fraction (FEA) 50 mg/kg BW. All treatments were given orally for 21 days and the data were analyzed by ANOVA and continued with the LSD post hoc test. HFD/HF induction significantly increased the HbA1c and AGEs levels 3.5 times and 1.88 times higher than the normal control group. Moreover, the treatments significantly reduced (p<0.05) HbA1c and AGEs levels compared to the negative control on day 21. Blood HbA1C levels with FEA treatment decreased by 56.4%, while AGEs reduced by 54.7%. GLUT 4 expression in the muscle tissue was significantly different from the negative control with p<0.05. The results also indicate that the administration of FEA had an antidiabetic effect by reducing the levels of HbA1C and AGEs along with other potentially beneficial effects on the treatment of type 2 DM with the probable mechanism of targeting GLUT4 glucose transporter by increasing its translocation and expression.